1991
DOI: 10.1099/0022-1317-72-6-1293
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses in mice following immunization with chimeric synthetic peptides representing B and T cell epitopes of measles virus proteins

Abstract: The immunogenicity of chimeric peptides produced by collinear synthesis to contain both T and B cell epitopes from the fusion protein and the haemagglutinin of measles virus was studied in mice. The T cell epitope used was from the fusion protein (residues 288 to 302), which has been shown to be promiscuous in its binding to mouse major histocompatibility complex molecules. This epitope was coupled by (i) a glycine-glycine spacer to a B cell epitope from the fusion protein (residues 404 to 414) and (ii) either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 31 publications
(24 reference statements)
0
20
0
Order By: Relevance
“…Other putative internal sequences showed little or no reactivity (peptides 30, 31, 61 to 63, 67, 71 and 96 to 98). In mice, peptide 52 induced antibodies, but these were not neutralizing [Partidos et al (1991) and our own results]. Like this T cell epitope described by Partidos and colleagues (Partidos & Steward, 1990;Partidos et al, 1991), other hidden sequences are also unlikely to be neutralizing.…”
Section: Discussionmentioning
confidence: 84%
“…Other putative internal sequences showed little or no reactivity (peptides 30, 31, 61 to 63, 67, 71 and 96 to 98). In mice, peptide 52 induced antibodies, but these were not neutralizing [Partidos et al (1991) and our own results]. Like this T cell epitope described by Partidos and colleagues (Partidos & Steward, 1990;Partidos et al, 1991), other hidden sequences are also unlikely to be neutralizing.…”
Section: Discussionmentioning
confidence: 84%
“…In our previous studies we have shown that the lack of immunogenicity of the 404-414 peptide can be overcome by the addition of a T-helper epitope (Partidos et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it has been demonstrated that a region represented by residues 404-414 is an important B-cell epitope. Anti-404-414 antibodies were shown to be reactive with MV in several strains of mice (Partidos et al, 1991), and confer protection in a mouse encephalitis model after collinear synthesis at the carboxyl terminus of two copies of a T-helper epitope (Obeid et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations